Woman’s representations in the scholar context back at the 50s: a study on the film “Mona Lisa Smile” (Research, Society and Development, 2020)
The study aims to analyze the representation of professors in the collective imaginary, starting from the cinema. This research was set off by selecting the North-American film Mona Lisa Smile (2003), intending to discuss perspectives about gender, reflecting about how the feminine stereotype, which is related to tenderness and maternity, is attached to the professor’s image in the 1950s. Therefore, two scenes of the film were analyzed with the intention of addressing the cinematographic discourse, in order to find possible answers for the questions of this work. As to theoretical support, we sought reflections about cinema, gender and the professor woman on authors such as Duarte (2000), Martin (2005), Beauvoir (1970), Butler (2010), Saffioti (2004) and Strey (1997). The results concluded that the cinematographic art, starting from the analyzed film, concerns itself on representing the fight for equal rights, autonomy and freedom for women within the labor context.